Optimisation of fragmentation at south deep gold fields mine: a case study - Nong, Matsobane (My University, 2020)
A fundamental aspect of an efficient mining operation is the steady movement of material throughout the mine system; particularly the flow of ore from the upstream excavation point to the downstream processing or stockpile site(s). This can be achieved by attaining an optimal fragmentation size from drilling and blasting suitable for subsequent mining process such as loading, hauling and crushing. Drilling and blasting are the first fragmentation process and is currently the most economical technique of fragmenting hard and competent rock especially for deep-level mines where operational costs are high. The aim of this research is to analyse and optimise fragmentation to improve the oreflow efficiency at South Deep Mine in South Africa. The mine experiences coarse fragmentation that cannot pass through 300mm by 300mm grizzlies. As such, secondary blasting is often done to reduce the size of boulders either in the stopes or on top of the grizzly which leads to a reduction in productivity. Although coarse fragmentation is reported in the stopes and on top of grizzlies, the plant is reporting fine fragmentation that is not suitable for the ball mill. This results in reduced gold recoveries. To get a better understanding of the fragmentation size distribution achieved, fifty-one images of the muckpile from five stopes were analysed using the Split-Desktop software. The analysis showed an overall F80 passing of 287.48mm, which is less than the 300mm grizzly size implying that the fragmentation size achieved is adequate. However, looking at the overall particle size, the Rosin-Rammler distribution was found to be 0.80. This infers an inconsistent fragmentation where the mine produces both coarse and fine fragmentation size. The AEGIS Underground drill and blast software was used to analyse the drill and blast design patterns. The analysis showed that the design toe spacing varies from about 0.5m to 7.5m in the same blast. Due to the software’s limitations, the break model analysis was only run for toe spacing between 2m and 7.5m. This showed that there is no overlap between blastholes which may be the source of the coarse fragmentation size. Fine fragment size may be as a result of blastholes which are close together, i.e. 0.5m. Although not tested, the impact of blasting stresses emanating from primary stopes may result in fractures in secondary stopes which will have a greater impact on the propagation of the shock wave and high-pressure gases between the blastholes and consequently the fragmentation distribution size. It is recommended that the mine change their drill and blast pattern. The mine must change from 76mm blasthole diameters and introduce a larger blasthole diameter of 89mm blasthole diameter. Not only will this diameter improve drilling accuracies but will reduce the fragmentation size distribution. It is also recommended that the mine maintains a ring burden of 2m throughout despite an increase in the blasthole diameter. For the first design, the toe spacing must also be 2m followed by increments of 0.5m per blast until a suitable fragmentation distribution size is achieved. After which, the toe spacing must be kept constant. It is important that South Deep Mine continually evaluate the fragmentation size distribution achieved from each blast for optimisation purposes. Therefore, a blast management system is important.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Mining Engineering, University of the Witwatersrand, 2020
Keywords: Mining operation; Mine oreflow